2008
DOI: 10.3844/ajabssp.2008.490.493
|View full text |Cite
|
Sign up to set email alerts
|

Improving a PCR-Based Method for Identification of Ralstonia solanacearum in Natural Sources of West Malaysia

Abstract: Ralstonia solanacearum, a soil-borne plant pathogen, causes lethal wilting disease of more than 200 plants worldwide. This very wide host range covers both monocots and dicots, extending from annual plants to trees and shrubs. Although generally it's considered as a plant pathogen, R. solanacearum behaves primarily as a saprophytic bacterium able to survive for long periods of time in various natural habitats such as surface waters and different types of soils. Epidemiological and ecological studies on pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Standardization of PCR and real time PCR analysis could play an important role for detection R. solanacearum from the disease in the seeds planting material, soil and irrigation water, where the pathogen survives in low number ( Table 1). The bacterial pathogen causing wilt disease can be detected by using conventional PCR with detection level from 10 2 cfu/ ml (Singh et al, 2014a) to 10 5 cfu/ ml (Khakvar et al, 2008). PCR based methods for the detection of R. solanacearum are usually based on the amplification of ribosomal sequences (16S rRNA or ITS region) and other conserved genes of bacteria (Pastrick et al, 2002;Ranajn et al, 2016;Singh et al, 2014a;Weller et al, 2000).…”
Section: Polymerase Chain Reaction (Pcr) Based Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Standardization of PCR and real time PCR analysis could play an important role for detection R. solanacearum from the disease in the seeds planting material, soil and irrigation water, where the pathogen survives in low number ( Table 1). The bacterial pathogen causing wilt disease can be detected by using conventional PCR with detection level from 10 2 cfu/ ml (Singh et al, 2014a) to 10 5 cfu/ ml (Khakvar et al, 2008). PCR based methods for the detection of R. solanacearum are usually based on the amplification of ribosomal sequences (16S rRNA or ITS region) and other conserved genes of bacteria (Pastrick et al, 2002;Ranajn et al, 2016;Singh et al, 2014a;Weller et al, 2000).…”
Section: Polymerase Chain Reaction (Pcr) Based Diagnosismentioning
confidence: 99%
“…Molecular based detection of R. solanacearum causing bacterial wilt of tomato, chilli, brinjal and potato has been done by using specific primers Y2 and OLII and it also distinguished R. solanacearum from other saprophytic bacteria grown on TTC medium (Singh et al, 2010(Singh et al, , 2014a. Various modifications have been made to improve the sensitivity of a single round PCR, viz., enrichment in semi-selective SMSA broth prior to PCR (Elphinstone et al, 1996;Ranjan et al, 2016;Singh et al, 2014a) or real time PCR called as BIO-PCR (Ozakman and Schaad, 2003) as well as double round PCR as nested-PCR (Khakvar et al, 2008). Grover et al (2009) detected R. solanacearum as low as 1 cfu/ml of within 8 h including DNA isolation.…”
Section: Polymerase Chain Reaction (Pcr) Based Diagnosismentioning
confidence: 99%
“…These primers have been reported that permit amplification of a fragment specifically from R. solanacearum (Seal et al, 1992(Seal et al, , 1993Seal and Elphinstone, 1994;Opina et al, 1997;Hartung et al, 1998;Ito et al, 1998). The rapidity and sensitivity of detection of R. solanacearum are desirable characteristics that have been met by the use of a nested-PCR procedure (McManus and Jones, 1995;Niepold and Schober-Butin, 1997;Khakvar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…1996) among which those based on PCR is most popular (Seal 1998). Ralstonia solanacearum can be detected in conventional PCR assay ranging from 10 2 CFU ml −1 (Khakvar et al. 2008) to 10 5 CFU ml −1 (Fegan et al.…”
Section: Introductionmentioning
confidence: 99%
“…enrichment in semiselective SMSA broth prior to PCR (Elphinstone et al. 1996), real‐time BIO‐PCR (Ozakman and Schaad 2003) and nested‐PCR (Khakvar et al. 2008).…”
Section: Introductionmentioning
confidence: 99%